Expanding to bulk: scale and the challenge of posthuman ethics in Moby-Dick. Issue 11 (2nd November 2021) - Hurh, Paul
ABSTRACT: Posthumanist theory has stressed the fictionality of accounts of human exceptionality and has viewed humans as particular sorts of things in a non-hierarchical relation with the universe of things. This approach has recently been taken up by nineteenth-century American literary scholarship through works by Michael Jonik, Cristin Ellis, Matthew Taylor, and others. However, because posthumanism can emphasise interconnection between human and nonhuman, it can run into difficulty, particularly in accounting for ethical imperatives. Drawing from Mark McGurl's theorisation of the giant as symbolic of the reality of physical forces, this essay considers how the size of the whale in Moby-Dick is a central descriptive problem of crossing scalar boundaries within a material field. What such a speculative reading offers is an understanding of Moby-Dick' s size as both a challenge and an affordance for the expansion of the human. Through prosthesis, the human may scale up to the whale's size, but that also entails a change of scalar field that disorients what such scaling procedures are for. Allowing for the difference between scales not only challenges narratives of human dominance in particular ways, but it also reveals, in Moby-Dick, an indication of a route towards a plural and posthuman ethics of discrete scales.